Colour analysis of potential natural colourant from Ixora siamensis and Melastoma malabathricum - Mohd-Adnan, A.F.; Nor, N.A.M.; Aziz, N.; Taha, R.M. (2011)
Anthocyanins are an important group of natural pigments that are responsible for many colours in plants. The variation in colour, depending on the pH, makes them a unique source of natural colourant. In this study, pigments from the fruits of Ixora siamensis and the fruit pulps of Melastoma malabathricum were extracted using trifluoroacetic acid-methanol solution. Spectral measurements (380-780 nm) were performed using visible spectroscopy with colour analysis software at different pHs (initial extracts were 1, 5, 7, 9 and 11). The colours of the solutions were expressed as colourimetric coordinates in the Commission Internationale de l'Eclairage (CIE) laboratory scale using L* (lightness), C* (chroma), H degrees (hue angle notation hab), a*/-a* (redness and greenness) and b*/-b* (blueness and yellowness) for the D65/2 degrees CIE Illuminant/Observer condition. In this work, the colour parameters were observed for natural colourant with and without blending with polyvinyl alcohol for both species (Ixora siamensis and Melastoma malabathricum). The relationships between the colour parameters (colourimetric indexes and CIELab variables) with pH variation and species dependence were discussed in this paper.